Dying is a solo - Wilson, Eva (Roma Publications, 2018)
This publication compiles material of performances and installations produced during a five year period, featuring scripts, and documentation of the works Ending with Glass, Learning to Imitate in Absentia, Obliterating an Image, The Distance between V and W, Objects in Diaspora, and A Reading That Loves - a Physical Act, of which the last was shown at Documenta 14. Yael Davids positions the reception of her performances and installations as a constitute force in her practice. Each performance repeats what has preceded, yet also expands, modifies, and nuances the previous version. Through this practice of perpetually attuning the central components of the work - voice, body and object - a series of augmented repetitions turns into a single composition, a single artwork
Titel vom Buchrücken
Keywords: Davids, Yael -- 1968-; Davids, Yael / 1968-; Bildband